Cassava reduces cost of chicken feed - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Trials have been carried out in Venezuela to substitute maize in chicken feed and replace it entirely with cassava-root flour. In the trials, both bitter and sweet cassava were used. Overall results indicated that it was feasible to totally...